2006
DOI: 10.1073/pnas.0605832103
|View full text |Cite
|
Sign up to set email alerts
|

Admixture mapping identifies 8q24 as a prostate cancer risk locus in African-American men

Abstract: A whole-genome admixture scan in 1,597 African Americans identified a 3.8 Mb interval on chromosome 8q24 as significantly associated with susceptibility to prostate cancer [logarithm of odds (LOD) ‫؍‬ 7.1]. The increased risk because of inheriting African ancestry is greater in men diagnosed before 72 years of age (P < 0.00032) and may contribute to the epidemiological observation that the higher risk for prostate cancer in African Americans is greatest in younger men (and attenuates with older age). The same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
482
7
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 579 publications
(515 citation statements)
references
References 23 publications
22
482
7
4
Order By: Relevance
“…[27][28][29][30] Recent studies, however, have shown considerable fractions of Amerindian ancestral component in many African-American individuals. 1,13 Using STRUCTURE, 31,32 we estimated the genetic contribution of African, European and Amerindian/East Asian populations to the 2114 African-Americans to be 0.725, 0.245 and 0.029, respectively (K ¼ 3).…”
Section: Lacs Distributions Facilitated Inference Of African-americanmentioning
confidence: 99%
“…[27][28][29][30] Recent studies, however, have shown considerable fractions of Amerindian ancestral component in many African-American individuals. 1,13 Using STRUCTURE, 31,32 we estimated the genetic contribution of African, European and Amerindian/East Asian populations to the 2114 African-Americans to be 0.725, 0.245 and 0.029, respectively (K ¼ 3).…”
Section: Lacs Distributions Facilitated Inference Of African-americanmentioning
confidence: 99%
“…http://doc.rero.ch [27][28][29][30][31]. However, multiple studies have identified genetic variants associated with lighter and darker skin pigmentation in humans [32][33][34], a trait that might be differentially selected in regions with low and high ultraviolet radiation (UVR), owing to known associations between skin pigmentation and vitamin D synthesis and protection from UVR [34,35].…”
Section: Box 2 Relationship Between Admixture and Association Mappingmentioning
confidence: 99%
“…Only when specific associations are validated in multiple large cohorts will the scientific community have confidence in the purported findings from such studies. Although it is currently unknown whether or not 8q24 is related to inflammatory pathways, one very recent example of a success story stems from a set of independent studies that implicated this chromosome region in prostate cancer occurring in both families and in sporadic cases 130,131 . …”
mentioning
confidence: 99%